Immunotherapy of Melanoma: Facts and Hopes - Weiss, Sarah A; Wolchok, Jedd D; Sznol, Mario (Clinical cancer research, 2019)
Melanoma is among the most sensitive of malignancies to immune modulation. Although multiple trials conducted over decades with vaccines, cytokines, and cell therapies demonstrated meaningful responses in a small subset of patients with metastatic disease, a true increase in overall survival (OS) within a randomized phase III trial was not observed until the development of anti-CTLA-4 (ipilimumab). Further improvements in OS for metastatic disease were observed with the anti-PD-1-based therapies (nivolumab, pembrolizumab) as single agents or combined with ipilimumab. A lower bound for expected 5-year survival for metastatic melanoma is currently approximately 35% and could be as high as 50% for the nivolumab/ipilimumab combination among patients who would meet criteria for clinical trials. Moreover, a substantial fraction of long-term survivors will likely remain progression-free without continued treatment. The hope and major challenge for the future is to understand the immunobiology of tumors with primary or acquired resistance to anti-PD-1 or anti-PD-1/anti-CTLA-4 and to develop effective immune therapies tailored to individual patient subsets not achieving long-term clinical benefit. Additional goals include optimal integration of immune therapy with nonimmune therapies, the development and validation of predictive biomarkers in the metastatic setting, improved prognostic and predictive biomarkers for the adjuvant setting, understanding mechanisms of and decreasing toxicity, and optimizing the duration of therapy.